2014
DOI: 10.1016/j.bjid.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon non-oncogenic HPV genotypes, TP53 and MDM2 genes polymorphisms in HIV-infected women in Southern Brazil

Abstract: The data obtained suggest that HIV-infected women are more susceptible to be infected by low-risk HPV (LR-HPV) genotypes than by high-risk (HR-HPV), and Pro72Pro of TP53 gene and TG of MDM2 SNP309 genotypes apparently seem to be protective factors among HIV-infected women for HPV acquisition and HR-HPV infection, respectively, in a sample of Southern Brazilian woman. Future investigations in larger populations are necessary to better understand the potential roles of these SNPs and the behavior of non-oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…This study found a prevalence of 28.4% of HR-HPV among women living with HIV/AIDS in Brazil. This result is lower than data described in previous studies in Rio de Janeiro (50.7%) 18 , Amazonas (61.6%) 19 and Rio Grande do Sul (68.0%) 20 . Some characteristics of these studies can explain the variety in the prevalence rates.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…This study found a prevalence of 28.4% of HR-HPV among women living with HIV/AIDS in Brazil. This result is lower than data described in previous studies in Rio de Janeiro (50.7%) 18 , Amazonas (61.6%) 19 and Rio Grande do Sul (68.0%) 20 . Some characteristics of these studies can explain the variety in the prevalence rates.…”
Section: Discussioncontrasting
confidence: 77%
“…Similar data was found in the Northeastern Brazil study, where the age < 35 years was more associated with HPV infection, principally with non 16/18 HR‐HPV . This result was different from another study conducted in South Brazil that found higher prevalence of HPV infection in WLHIV with 40 or more years old . However a study in Sub‐Saharan Africa also found higher prevalence of HPV in younger (18‐25) WLHIV, although the authors did not found a tendency of decreasing HPV prevalence with increasing age .…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations